Pengaruh Motivasi Kerja terhadap Kinerja Staf Sumber Daya Manusia pada Kantor Polres Pelabuhan Kota Makassar - Nursiah Abdullah; Dahlan (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2024)
This study aims to determine the Influence of Work Motivation on the Performance of Human Resources Staff at the Makassar City Harbor Police Office. The type of research used is quantitative research. This research was conducted at the Makassar City Harbor Police Office. The population and sample of the study were all Human Resources staff at the Makassar City Harbor Police Office as many as 42 people. Data collection used observation, interview and questionnaire techniques. The data analysis used was simple linear regression analysis. The results of the analysis found that Motivation had a positive and significant effect on the Performance of Human Resources (HR) Staff at the Makassar City Harbor Police Office. This can be seen from the results of the t-test showing that the t value of 10.164 is greater than t 2.108 with a probability value of 0.000 less than 0.05 which means that the hypothesis in this study has been proven and can be accepted. The results of the correlation analysis obtained a correlation coefficient (R) of 0.849 which means that the relationships between motivation variables (X) and employee performance (Y) at the Makassar City Harbor Police Office are positive and very close.